Juridical Analysis Of The Implementation Of Criminal Tax Offense Decisions (Case Study: Decision Of Case Number: 387/Pid.Sus/2022/Pn Plg At The Palembang District Court) - Yunianto, Ari; Lubis, Muhammad Dhobit Azhary (Jurnal Indonesia Sosial Sains, 2025)
The Harmonization of Tax Regulations Law of 2021 plays a crucial role in strengthening the enforcement of tax crimes in Indonesia. This law prioritizes the recovery of state losses over solely punishing offenders through imprisonment.. Article 44B, paragraph 2a, stipulates that convicts are given the opportunity to make payments to recover state losses, extending this possibility up to the trial stage (HPP Law, 2021). Furthermore, Article 44C, paragraph (1) states that fines as referred to in Article 39 and Article 39A cannot be substituted with imprisonment and must be paid by the convict (HPP Law, 2021).To ensure a deterrent effect on tax offenders—considering the severe impact of tax crimes on state revenues—Article 39, paragraph (1) emphasizes that any person who deliberately commits actions specified in points (a) to (i), resulting in state revenue losses, shall be punished with a minimum prison sentence of six (6) months and a maximum of six (6) years (HPP Law, 2021). The emphasis is on imprisonment without the possibility of probation. As law enforcement officials, judges play a crucial role in the trial process, serving as decision-makers in tax dispute cases. Their role is essential in maximizing the recovery of state revenue losses and ensuring preventive measures. However, in practice, the implementation of tax crime rulings by judges has exhibited errors, leading to legal uncertainty. This, in turn, results in inadequate recovery of state revenue losses and a suboptimal deterrent effect on offenders.